FREQUENCY OF HYPERURICEMIA IN METABOLIC SYNDROME (Journal of Medical & Health Sciences Review, 2025)
Background: Metabolic syndrome (MetS) is the co-occurrence of cardiovascular risk factors that include obesity, hypertension, dyslipidemia and insulin resistance. Hyperuricemia is frequently observed in people with MetS and may contribute to cardiovascular and renal risk. Because hyperuricemia commonly co-occurs with MetS components, establishing its prevalence may improve cardiometabolic risk stratification and prevention of renal and cardiovascular complications.Objectives: To determine the prevalence of hyperuricemia in individuals with metabolic syndrome and its association with patient age, sex, or other demographic parameter of the patients or also to their other metabolic risk factors and overall disease burden in our study population cohort.Study Design: A cross-sectional study.Place and Duration of study: From December 2024 to May 2025 in General Medicine Department, Bolan Medical Complex Hospital Quetta. Methods: A cross-sectional study was conducted in the Department of Medicine, Bolan Medical Complex Hospital, Quetta from December 2024 to May 2025, including 120 patients with metabolic syndrome (NCEP-ATP III criteria). Serum uric acid was measured enzymatically; hyperuricemia was defined as >7.0 mg/dL in men and >6.0 mg/dL in women. Demographic, clinical, and biochemical data were collected. Exclusions included CKD, gout, hematological disorders, or uric acid–altering medications. Data were analyzed using SPSS 24, with t-tests and chi-square tests (p